Inactivation of the three GGA genes in HeLa cells partially compromises lysosomal enzyme sorting. Issue 2 (1st January 2021) - Doray, Balraj; Liu, Lin; Lee, Wang‐Sik; Jennings, Benjamin C.; Kornfeld, Stuart
Abstract : The Golgi‐localized, gamma‐ear containing, ADP‐ribosylation factor‐binding proteins (GGAs 1, 2, and 3) are multidomain proteins that bind mannose 6‐phosphate receptors (MPRs) at the Golgi and play a role, along with adaptor protein complex 1 (AP‐1), in the sorting of newly synthesized lysosomal hydrolases to the endolysosomal system. However, the relative importance of the two types of coat proteins in this process is still unclear. Here, we report that inactivation of all three GGA genes in HeLa cells decreased the sorting efficiency of cathepsin D from 97% to 73% relative to wild‐type, with marked redistribution of the cation‐independent MPR from peripheral punctae to the trans ‐Golgi network. In comparison, GNPTAB −/− HeLa cells with complete inactivation of the mannose 6‐phosphate pathway sorted only 20% of the cathepsin D. We conclude that the residual sorting of cathepsin D in the GGA triple‐knockout cells is mediated by AP‐1. Abstract : In this study, we inactivated all three GGA genes in HeLa cells using CRISPR‐Cas9 genome editing. The GGA triple‐knockout cells secreted 27% of newly synthesized cathepsin D, compared to 2.6% secretion seen with wild‐type HeLa cells. In contrast, HeLa cells with complete inactivation of the mannose 6‐phosphate pathway secreted 77.5% of the newly synthesized cathepsin D.